Cohort profile: an observational population-based cohort study on COVID-19 vaccine effectiveness in the Netherlands – the VAccine Study COVID-19 (VASCO) - Diederick E Grobbee; Gerco den Hartog; Hester E de Melker; Susan van den Hof; Marjolein N Kooijman; Anne J Huiberts; Christina E Hoeve; Susan JM Hahné; Rob van Binnendijk; Janneke HHM van de Wijgert; Mirjam J Knol (BMJ Open)
Purpose VAccine Study COVID-19 (VASCO) is a cohort study with a 5-year follow-up that was initiated when COVID-19 vaccination was introduced in the Netherlands. The primary objective is to estimate real-world vaccine effectiveness (VE) of COVID-19 vaccines against SARS-CoV-2 infection in the Netherlands, overall and in four subpopulations defined by age and medical risk.Participants The cohort consists of 45 547 community-dwelling participants aged 18–85 years who were included irrespective of their COVID-19 vaccination status or intention to get vaccinated. A medical risk condition is present in 4289 (19.8%) of 21 679 individuals aged 18–59 years, and in 9135 (38.3%) of 23 821 individuals aged 60–85 years. After 1 year of follow-up, 5502 participants had dropped out of the study. At inclusion and several times after inclusion, participants are asked to take a self-collected fingerprick blood sample in which nucleoprotein and spike protein receptor binding domain-specific antibody concentrations are assessed. Participants are also asked to complete monthly digital questionnaires in the first year, and 3 monthly in years 2–5, including questions on sociodemographic factors, health status, COVID-19 vaccination, SARS-CoV-2-related symptoms and testing results, and behavioural responses to COVID-19 measures.Findings to date VASCO data have been used to describe VE against SARS-CoV-2 infection of primary vaccination, first and second booster and bivalent boosters, the impact of hybrid immunity on SARS-CoV-2 infection and VE against infectiousness. Furthermore, data were used to describe antibody response following vaccination and breakthrough infections and to investigate the relation between antibody response and reactogenicity.Future plans VASCO will be able to contribute to policy decision-making regarding future COVID-19 vaccination. Furthermore, VASCO provides an infrastructure to conduct further studies and to respond to changes in vaccination campaigns and testing policy, and new virus variants.Trial registration number NL9279.